The Satisfaction Level of Science and Mathematics Teachers with Their School Principals as Resident Supervisors in Enhancing Students’ Learning - Ali Khaled Bawaneh; Yazan M. Alghazo; Belal S. Rabab'h; Abdulghani Al-Hattami (Scientia Publica Media, 2025)
The purpose of this study was to examine the satisfaction levels of Jordanian science and mathematics teachers regarding the school principal’s role as a resident supervisor. The target population consisted of all Jordanian science and mathematics teachers, from which a sample of 212 male and female teachers was drawn. Data were obtained through a researcher-designed questionnaire, the validity and reliability of which were established prior to its administration. The instrument was disseminated electronically to participants using the snowball sampling method. Findings revealed that the overall satisfaction of Jordanian science and mathematics teachers with the principal’s role as a resident supervisor fell within the high category. Moreover, no significant differences were identified in teachers’ satisfaction levels based on gender, years of teaching experience, type of school (public or private), or area of specialization (science or mathematics). Findings concluded that the role of the school principal as resident supervisor has become a necessity rather than just an option. Accordingly, the study reached several recommendations: maintaining the promotion of the culture of resident supervision, strengthening the factors that increase the level of teachers’ satisfaction with their principals, and achieving fairness, regardless of the gender of the teacher and school principal, specialization, type of school (government or private sector), experience, academic degree, and other variables strengthening the integrated relationship between school principals, teachers, students, and the local community. This study aims to investigate the relationship of teachers with educational supervision, parents, and their relationship with each other. Researchers can also conduct studies to investigate the impact of the role of the school principal as a mentor in improving the performance of teachers and students.